Analisis Perbedaan Abnormal Return Pada Perusahaan Merger dan Akuisisi - Sukmajati, Amru (Graduasi: Jurnal Bisnis & Ekonomi, 2012)
This research aims to determine the difference in abnormal returns generated by the company before and after mergers and acquisitions. Measurement variables used in this study is Cumulative Abnormal Return (CAR) which is divided into several event window that is CAR-20,-2; CAR0; CAR1, - 1; and CAR2, 20. It is also used abnormal return for each day during 41 days of observation. The study found no significant abnormal return on announcement of mergers and acquisitions. Other results show, there were no differences in abnormal return for each event window periods being compared. While on the daily abnormal stock returns for 41 days were compared in pairs, obtained the result that there are significant differences in abnormal return in a few days before and after mergers and acquisitions